Analysis of Intra-Community Foreign Trade of Poland on the Basis of Mirror Data - Paweł BARAN; Iwona MARKOWICZ (Communications of International Proceedings, 2020)
In Poland, after the accession to the European Union in 2004, an obligation to submit Intrastat declarations exists. The obligation applies to entities dealing with intra-Community trade in all EU countries. Statistical data are collected in individual countries (Intrastat system) and then transmitted to Eurostat. These data are symmetrical and often inconsistent. For example: there is a difference between two sets of data – data on intra-Community supply of goods (ICS) sent from Poland and data on intra-Community acquisition (ICA) coming from Poland (mirror data). The authors examine these differences broken down by Combined Nomenclature chapters and by trade partner countries. The aim of the article is to show how the selection of one of the above-mentioned data sources may influence the results of the analyses. The research was conducted on the example of Poland’s trade with the EU Member States turnover. The ordering of EU countries according to the turnover and classification of countries according to the structure of goods (CN nomenclature chapters) in the scope of ICS-ICA (Poland-EU countries) and comparison of the results of the classification in time were carried out. We prove that ICS and ICA data from 2017 are more similar in structure to ICS and ICA data from 2016 respectively than to their mirror dataset from the same year.
Keywords: Intra-Community Foreign Trade; Mirror Data; Cluster Analysis; Public Statistics; Intrastat